Enhancing the role of livestock in poverty reduction strategies: Analytical approaches and applications. Abstract - Freeman, H.A.; Minjauw, B. (2005)
This paper presents a proposal description. The proposal describes analytical work by the International Livestock Research Institute and its partners on livestock and poverty reduction. It also provides some insights into the practical and potential application of the results from livestock and poverty analysis in the design of poverty policies, projects, and strategy formulation. Past research undertaken by ILRI and its partners on livestock and poverty reduction has focused on poverty diagnostics. This work provided answers to policy relevant questions such as where are the poor livestock keepers; where are the poor; what explains pathways into and out of poverty and the role of livestock in these processes. The result from the research on where are the poor livestock keepers produced maps and tables that show the location of significant populations of poor livestock keepers worldwide and assessed how these populations are likely to change over the next 30 to 50 years.